TIP60: an actor in acetylation of H3K4 and tumor development in breast cancer. (16th October 2018) - Judes, Gaëlle; Dubois, Lucas; Rifaï, Khaldoun; Idrissou, Mouhamed; Mishellany, Florence; Pajon, Amaury; Besse, Sophie; Daures, Marine; Degoul, Françoise; Bignon, Yves-Jean; Penault-Llorca, Frédérique; Bernard-Gallon, Dominique
Aim: The acetyltransferase TIP60 is reported to be downregulated in several cancers, in particular breast cancer, but the molecular mechanisms resulting from its alteration are still unclear.Materials & methods: In breast tumors, H3K4ac enrichment and its link with TIP60 were evaluated by chromatin immunoprecipitation-qPCR and re-chromatin immunoprecipitation techniques. To assess the biological roles of TIP60 in breast cancer, two cell lines of breast cancer, MDA-MB-231 (ER-) and MCF-7 (ER+) were transfected with shRNA specifically targeting TIP60 and injected to athymic Balb-c mice.Results: We identified a potential target of TIP60, H3K4. We show that an underexpression of TIP60 could contribute to a reduction of H3K4 acetylation in breast cancer. An increase in tumor development was noted in sh-TIP60 MDA-MB-231 xenografts and a slowdown of tumor growth in sh-TIP60 MCF-7 xenografts.Conclusion: This is evidence that the underexpression of TIP60 observed in breast cancer can promote the tumorigenesis of ER-negative tumors.